2020
DOI: 10.24075/brsmu.2020.080
|View full text |Cite
|
Sign up to set email alerts
|

Cartographic atlas of frequency variation for 45 pharmacogenetic markers in populations of Russia and its neighbor states

Abstract: The lack of information about the frequency of pharmacogenetic markers in Russia impedes the adoption of personalized treatment algorithms originally developed for West European populations. The aim of this paper was to study the distribution of some clinically significant pharmacogenetic markers across Russia. A total of 45 pharmacogenetic markers were selected from a few population genetic datasets, including ADME, drug target and hemostasis-controlling genes. The total number of donors genotyped for these m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Moreover, extrapolating a MAF from one population to another may not be straightforward as different variants may follow different geographical distribution patterns. For instance, Balanovskaya and others used a cartographic approach (2,197 participants representing 50 different populations/137 ethnic and subethnic groups) to visualize the geographic distribution of pharmacogenetic markers across Russia and its neighbouring countries and reported that: CYP2C9*2 followed a focal variation pattern [the CYP2C9*2 allele was specific to certain ethnicities (MAF as high as 0.23) and absent in others]; CYP2C9*3 followed a uniform pattern [MAF varying within a narrow range (0.03 to 0.10) in most ethnic groups]; and VKORC1 -1639G > A followed a clinal pattern [a gradient decrease in MAF (from >0.95 to ∼0.30) along the East-West axis] ( Balanovskaya et al, 2020 ).…”
Section: Genetic Variants Influencing Warfarin Responsementioning
confidence: 99%
“…Moreover, extrapolating a MAF from one population to another may not be straightforward as different variants may follow different geographical distribution patterns. For instance, Balanovskaya and others used a cartographic approach (2,197 participants representing 50 different populations/137 ethnic and subethnic groups) to visualize the geographic distribution of pharmacogenetic markers across Russia and its neighbouring countries and reported that: CYP2C9*2 followed a focal variation pattern [the CYP2C9*2 allele was specific to certain ethnicities (MAF as high as 0.23) and absent in others]; CYP2C9*3 followed a uniform pattern [MAF varying within a narrow range (0.03 to 0.10) in most ethnic groups]; and VKORC1 -1639G > A followed a clinal pattern [a gradient decrease in MAF (from >0.95 to ∼0.30) along the East-West axis] ( Balanovskaya et al, 2020 ).…”
Section: Genetic Variants Influencing Warfarin Responsementioning
confidence: 99%